Paradoxical puborectalis syndrome on diffusion-weighted imaging: a retrospective study of 72 cases - Guiqin Liu (Nature Portfolio, 2017)
Abstract This study aimed to evaluate the application value of diffusion-weighted imaging (DWI) for assessing paradoxical puborectalis syndrome (PPS) in patients with obstructive defecation syndrome (ODS). The medical records of 72 ODS patients who underwent magnetic resonance (MR)-DWI and MR-defecography were retrospectively reviewed. The differences in the apparent diffusion coefficients (ADCs) and the thickness of the right and left branches of the puborectalis muscles between the PPS(+) and PPS(−) groups were compared. In addition, the absolute within-patient differences between the right and left branches (ADC, thickness) were compared between the two groups. The absolute difference in ADCs (right branch - left branch) was significantly different between the two groups. Regardless of whether the ADC was acquired through single-ROI (0.10 ± 0.08 vs 0.23 ± 0.18, P = 0.000) or multi-ROI (0.16 ± 0.14 vs 0.27 ± 0.17, P = 0.009) analysis, the PPS(+) patients displayed a lower absolute ADC difference than did the PPS(−) patients. However, there was no statistically significant difference in the ADC value, thickness or the absolute difference in thickness between the two groups. These findings suggest that DWI may have value in quantitatively assessing the puborectalis muscle in ODS patients, whereas the value of puborectalis thickness in such aspect needs further study.